Inkspell eaudiobook - Funke, Cornelia (Inkworld, 2006)
Although a year has passed, not a day goes by without Meggie thinking of Inkheart , the book whose characters came to life - and changed her life forever. But for Dustfinger, the fire-eater brought into being from words, the need to return to the original tale has become desperate. When he finds a crooked storyteller with the magical ability to read him back, Dustfinger leaves behind his young apprentice Farid and plunges into the medieval inkscape once more. Distraught, Farid goes in search of Meggie, and before long both are caught inside the book, too. There they meet Inkheart 's author, Fenoglio, now living within his own story. But the tale is much changed, and threatening to evolve in ways none of them would have ever imagined. Will Meggie, Farid, and Fenoglio manage to write the wrongs of a charmed world? Or is their story on the brink of a very bad ending?